2016
DOI: 10.1128/jvi.03175-15
|View full text |Cite
|
Sign up to set email alerts
|

αvβ3 Integrin Boosts the Innate Immune Response Elicited in Epithelial Cells through Plasma Membrane and Endosomal Toll-Like Receptors

Abstract: We report that ␣v␤3 integrin strongly affects the innate immune response in epithelial cells. ␣v␤3 integrin greatly increased the response elicited via plasma membrane Toll-like receptors (TLRs) by herpes simplex virus or bacterial ligands. The endosomal TLR3, not the cytosolic sensor interferon gamma-inducible protein 16 (IFI16), was also boosted by ␣v␤3 integrin. The boosting was exerted specifically by ␣v␤3 integrin but not by ␣v␤6 or ␣v␤8 integrin. Current and previous work indicates that integrin-TLR coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…In support of an important role for the gH-integrin interaction it was shown that siRNA knockdown of αvβ3 prevents HSV entry (69). Consistent with these results, work from the Campadelli-Fiume laboratory has demonstrated an important role for integrins in HSV infection (8, 10, 35, 7274). They have proposed that these integrins serve as co-receptors.…”
Section: Signaling Pathways Affected By Herpesvirus Glycoproteinssupporting
confidence: 66%
See 1 more Smart Citation
“…In support of an important role for the gH-integrin interaction it was shown that siRNA knockdown of αvβ3 prevents HSV entry (69). Consistent with these results, work from the Campadelli-Fiume laboratory has demonstrated an important role for integrins in HSV infection (8, 10, 35, 7274). They have proposed that these integrins serve as co-receptors.…”
Section: Signaling Pathways Affected By Herpesvirus Glycoproteinssupporting
confidence: 66%
“…For equine herpesvirus 1(EHV-1), another alphaherpesvirus, it has been shown that binding of gH to α4β1 integrin induces calcium signaling and that abrogation of this pathway redirects entry to the endocytic pathway (38). Multiple groups have shown that gH-integrin complex formation requires the presence of other fusion complex members, such as gD and gB to function (10, 71), implying that either gD receptor binding, or fusion complex formation is important for subsequent gH-integrin complex formation.…”
Section: Signaling Pathways Affected By Herpesvirus Glycoproteinsmentioning
confidence: 99%
“…Recently, Casiraghi et al reported that ␣v␤3 integrin strongly affects the innate immune response in epithelial cells. They showed that ␣v␤3 integrin greatly increased the immune response elicited by herpes simplex virus, which had previously been shown to bind ␣v␤3 integrin (42). This implies that HAdV26 interaction with ␣v␤3 integrin might also influence the innate immune response in infected cells, and therefore, it would be interesting to investigate it in more detail.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, internalized integrins cosignal with these receptors from endosomes toward the extracellular signal-regulated kinase (ERK) and AKT pathways, to synergistically drive cell proliferation and survival [ 91 , 92 ]. Some integrins mediate phagocytosis of (complement-opsonized) pathogens, such as herpes simplex virus and Listeria monocytogenes [ 99 , 100 ]. Following internalization, these integrins can induce the recruitment of microtubule-associated protein 1A/1B light chains 3B (LC3) to form autophagosomes, which fuse with lysosomes to degrade the pathogens [ 94 , 95 ].…”
Section: Integrin-dependent Vesicular Trafficking Regulates Receptor mentioning
confidence: 99%